PEMERINTAH REPUBLIK INDONESIA MENGHADAPI KLAIM BUDAYA KUDA LUMPING OLEH MALAYSIA TAHUN 2017 - Koni Larasati; Christy Damayanti; GPH Dipokusumo (Solidaritas, 2020)
This study explains how the Government of the Republic of Indonesia faces the claims of kuda lumping culture by Malaysia in 2017. The method used in this study is a qualitative method which is described descriptively using primary data sources and secondary data. Sources of data in this research the authors get from books, journals, documents, magazines, and materials from the internet. Primary data is data obtained directly through interviews with informants. From the data obtained by researchers about the Government of the Republic of Indonesia facing the kuda lumping claim by Malaysia in 2017, it was diplomatically organized by the Indonesian Embassy in Kuala Lumpur and technically by the Indonesian Ministry of Education and Culture.